Magnetic nano antibacterial compound as well as preparation method and application thereof

Through the preparation of the magnetic nano-bacterial antibacterial complex Fe3O4@ZnO, the problems of microbial growth and mycotoxin metabolism in corn storage are solved, effective antibacterial effect is achieved and material recycling is promoted, providing an environmentally friendly and economical anti-mold solution.

CN119791160APending Publication Date: 2025-04-11HENAN UNIVERSITY OF TECHNOLOGY
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411800084.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-09
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

During corn storage, due to the growth and reproduction of microorganisms and the metabolism of mycotoxins, the problems of food quality, mold and grain pile heat are difficult to effectively solve.

Method used

Fe3O4 nanoparticles were prepared by ion co-precipitation method using magnetic nanobacterial inhibition complex Fe3O4@ZnO, and the ZnO nanoparticles were covalently combined with Fe3O4 nanoparticles through heating synthesis to form a stable magnetic nanobacterial inhibition complex.

Benefits of technology

This magnetic nano-anti-bacterial complex significantly inhibits microbial growth and mycotoxin metabolism during corn storage, prevents mildew and grain piles from heating, and is magnetically recyclable, realizing the recycling of antibacterial materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119791160A_ABST
    Figure CN119791160A_ABST
Patent Text Reader

Abstract

The invention discloses a magnetic nano antibacterial compound and a preparation method and application thereof, and relates to the field of antibacterial materials, and the preparation method comprises the following steps: S1, dissolving ferric salt and ferrous salt in a hydrochloric acid solution, heating, adding an ammonia solution, separating out generated precipitate particles, dispersing the precipitate particles in a tetramethylammonium hydroxide solution, separating out the precipitate particles again, and washing to obtain a magnetic nano antibacterial compound; the Fe3O4 nano particles are obtained; and S2, dispersing the Fe3O4 nanoparticles in diethylene glycol, adding a diethylene glycol solution of zinc acetate, uniformly stirring, heating to 160-220 DEG C in a closed manner, keeping the temperature for 1.5-2.5 hours, washing, and magnetically separating precipitate particles, thereby obtaining the magnetic nano antibacterial compound. Through covalent interaction and combination with small-particle-size ZnO-NPs obtained through polyhydric alcohol mediation, the stable magnetic nano antibacterial compound is obtained and used for efficiently inhibiting microorganism growth and reproduction and mycotoxin metabolism in the corn storage process, and directional movement and simple and convenient recovery of the nano antibacterial compound can also be achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of antibacterial materials, in particular to a magnetic nano antibacterial composite and a preparation method and application thereof. Background Art

[0002] As a living organism, grains will constantly breathe, synthesize, and decompose, whether in the field or after harvest. In particular, the embryo of corn is large and nutritious, which can easily become a hotbed for microbial reproduction, causing a significant reduction in grain quality. At the same time, the heating of the grain pile caused by the growth and reproduction of microorganisms will further aggravate the deterioration of corn, and the metabolized fungal toxins will directly threaten people's lives and health. In large grain piles, the microenvironments such as temperature, humidity, and oxygen concentration at different grain pile sites have certain differences, resulting in large differences in the growth and reproduction rates of microorganisms at different grain pile locations. In addition, during the storage of corn, the local grain condition is poorly stable, which can easily cause local sites in the grain pile to heat up and cause mold.

[0003] Corn is prone to mildew and excessive mycotoxins due to its high moisture content, rich nutrients, and large amount of bacteria. Relevant studies have shown that the dominant microorganisms in corn include Enterococcus, Pantoea, Fusarium, Penicillium, and Aspergillus. Enterococcus and Pantoea are both conditional pathogens for humans; Fusarium has the ability to infect foods such as grains, dairy products, meat, and fruits, causing food to spoil and metabolize to produce a large amount of zearalenone and fumonisins, which threaten people's health; Penicillium and Aspergillus are also the main fungi that cause corn and other crops to spoil, and the aflatoxin B1 they produce is highly carcinogenic to humans. How to effectively extend the storage period of grain, ensure the stability of grain quality, and reduce the loss of grain during storage has long been a major problem that needs to be solved in the field of grain storage. With the continuous development of science and technology, nanomaterials, as a material with special structure and properties, provide new possibilities for solving problems encountered in the grain storage process.

[0004] Zinc oxide nanoparticles are a common inorganic antibacterial material. They have a broad antibacterial spectrum, long antibacterial time, low environmental requirements, good antibacterial effect, and are non-toxic and harmless. They have been widely used in food, packaging, textile and other industries. They can also be used for antibacterial treatment in grain fields, thus playing a certain role in antibacterial properties. Zinc oxide has been widely used as an additive in the feed industry. Compared with other similar oxides, it has unique advantages such as good biocompatibility, large specific surface area, non-toxicity, good chemical stability and low cost. Fe3O4 is the main component of magnetite. It is the earliest magnetic material put into use in the world. Because of its simple preparation process and strong adsorption capacity, it is widely used in the research and application of magnetic materials. The Fe3O4 nanoparticles prepared by ion co-precipitation have a small particle size and a simple process, and are now widely used. The ion co-precipitation method is to convert Fe 2+ with Fe 3+ After the chloride solution is mixed in a certain proportion (generally the molar ratio is 1:2 or 2:3), it is stirred evenly during the reaction at a certain temperature and pH, and a precipitate is obtained by high-speed centrifugation. The precipitate is washed and freeze-dried to obtain nano-sized Fe3O4 particles.

[0005] There are some methods disclosed in the prior art for compounding Fe3O4 and zinc oxide to obtain Fe3O4 / ZnO composites, such as the Chinese invention patent with publication number CN 104815610 A, the patent name of which is an adsorbent based on ferroferric oxide and nano zinc oxide and its preparation method; and the Chinese invention patent with publication number CN 109225236 A, the patent name of which is a Fe3O4 / ZnO magnetic nano antibacterial composite and its synthesis method. However, the Fe3O4 / ZnO magnetic nano antibacterial composites prepared by these methods are mostly used as adsorbents or for photocatalysis and removal of water pollutants, and there are no clear requirements for the control of the particle size of ZnO nanoparticles, especially the combination mode of Fe3O4 and ZnO. On the basis of further controlling the morphology, particle size and dispersibility of ZnO nanoparticles, there are few reports on the research of introducing the magnetic properties of Fe3O4 nanoparticles into the nano antibacterial composite to improve the antibacterial efficiency and recycling efficiency of this type of nano composite. Summary of the invention

[0006] The present invention provides a magnetic nano antibacterial composite and a preparation method and application thereof, so as to effectively inhibit the growth and reproduction of microorganisms and the metabolism of fungal toxins during the storage of corn.

[0007] In order to achieve the above object, the specific scheme adopted by the present invention is: a method for preparing a magnetic nano antibacterial composite, comprising the following steps:

[0008] S1: dissolving iron salt and ferrous salt in hydrochloric acid solution, heating, adding ammonia solution, separating generated precipitated particles, dispersing the precipitated particles in tetramethylammonium hydroxide solution, separating the precipitated particles again and washing them to obtain Fe3O4 nanoparticles;

[0009] S2: Disperse Fe3O4 nanoparticles in diethylene glycol, add diethylene glycol solution of zinc acetate, stir evenly, heat to 160-220°C in a sealed container and keep warm for 1.5-2.5 hours, wash, and magnetically separate the precipitated particles to obtain the magnetic nano antibacterial complex.

[0010] As a further optimization of the above technical solution: the iron salt described in step S1 is one or more of FeCl3, FeCl3·6H2O, Fe2(SO4)3 and Fe2(NO3)3; the ferrous salt is one or more of FeSO4, FeSO4·7H2O, FeCl2 and FeNO3.

[0011] As a further optimization of the above technical solution: in step S1, Fe 3+ and Fe 2+ The molar ratio is ≥1.5.

[0012] As a further optimization of the above technical solution: in step S1, after the iron salt and the ferrous salt are dissolved in the hydrochloric acid solution, the temperature is raised to 55-65° C., and then the ammonia solution is added.

[0013] As a further optimization of the above technical solution: in step S1, the pH of the tetramethylammonium hydroxide solution is 9.5-10.5.

[0014] As a further optimization of the above technical solution: in step S2, heat to 180-200°C in a sealed manner and keep warm for 1.5-2h.

[0015] As a further optimization of the above technical solution: in step S2, in step S2, after heat preservation, centrifugation is performed to obtain the precipitate, and then washing is performed. The centrifugal speed is 7000-10000 rpm, and the centrifugation time is 10-18 min.

[0016] A magnetic nano antibacterial composite is prepared by any of the above preparation methods.

[0017] The invention discloses an application of a magnetic nano antibacterial compound as a bacterial antibacterial agent or a mold antibacterial agent.

[0018] A magnetic nano-antibacterial complex can inhibit the metabolism of mycotoxins in molds.

[0019] The invention discloses an application of a magnetic nano antibacterial compound in corn storage, wherein the magnetic nano antibacterial compound is evenly dispersed on the surface of corn kernels by spraying or stirring.

[0020] As a further optimization of the above technical solution: magnetic attraction, movement and adsorption recovery of the nano antibacterial complex can be achieved by placing magnets at fixed points.

[0021] Compared with the prior art, the present invention has the following beneficial effects:

[0022] A magnetic nano antibacterial composite having both antibacterial properties and magnetism is prepared by the method of the present invention. The metal bonds rich on the surface of the magnetic core are covalently bonded with the metal bonds on the surface of the antibacterial material, and the small-size antibacterial material is aggregated around the magnetic core, which also increases the controllability of the small-size nanoparticles. In the preparation process, the present invention utilizes the reduction characteristics of DEG to a suitable metal precursor (Zn), and obtains a suspension of metal oxide nanoparticles in a simple manner by heating a DEG solution of a suitable metal salt, and uniformly disperses Fe3O4 nanoparticles in DEG. In the process of uniform stirring, the Fe3O4 nanoparticles are combined with the small-size ZnO-NPs obtained by polyol mediation through covalent interaction, thereby obtaining a stable magnetic nano antibacterial composite. As an active metal element, zinc has a large number of Zn-O bonds on its oxide surface, which can form a stable covalent bond with the Fe-O bonds in Fe3O4, thereby improving the stability of the prepared Fe3O4@ZnO magnetic nano antibacterial composite.

[0023] The present invention enhances the antibacterial ability of the material by reducing the particle size of zinc oxide nanoparticles. When the prepared magnetic nano antibacterial composite is used in corn storage, the material can be recovered by utilizing the magnetism of the material, thereby realizing the recycling of the antibacterial material.

[0024] The Fe3O4@ZnO prepared by the present invention has a significant inhibitory effect on the growth and reproduction of dominant bacteria Enterococcus and Pantoea and dominant molds Fusarium, Aspergillus and Penicillium in the corn storage process. At the same time, the addition of the composite effectively prevents the problems of grain pile heating, mildew, excessive fungal toxins, etc. in the corn storage process. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 Schematic diagram of the synthesis of Fe3O4@ZnO nanocomposites;

[0026] Figure 2 TEM spectra of Fe3O4 nanoparticles (A) and Fe3O4@ZnO nanocomposites (B); element mapping spectra of Fe (C), Zn (D), and Fe and Zn superposition (E); EDX of the prepared Fe3O4@ZnO nanocomposites (F); XRD spectra of Fe3O4 and Fe3O4@ZnO nanocomposites (G); IR spectra of Fe3O4 and Fe3O4@ZnO nanocomposites (H);

[0027] Figure 3 The state of Fe3O4@ZnO nanocomposite before and after magnet adsorption

[0028] Figure 4 The antibacterial activity of Fe3O4@ZnO nanocomposites with different concentrations against Enterococcus and Pantoea;

[0029] Figure 5 The antibacterial activity of Fe3O4@ZnO nanocomposites with different concentrations against Penicillium and Aspergillus niger;

[0030] Figure 6 The effects of different concentrations of Fe3O4@ZnO nanocomposites on Pantoea and Enterococcus;

[0031] Figure 7 The effects of different concentrations of Fe3O4@ZnO nanocomposites on Penicillium and Aspergillus niger;

[0032] Figure 8 The inhibition of the total bacterial colony count by Fe3O4@ZnO nanocomposites;

[0033] Fig. 9 The inhibition of the total number of fungal colonies by Fe3O4@ZnO nanocomposites;

[0034] Fig.10 The inhibition of aflatoxin B1 metabolism by Fe3O4@ZnO nanocomposites;

[0035] Fig.11 The inhibition of DON metabolism by Fe3O4@ZnO nanocomposites;

[0036] Fig.12 The inhibition of zearalenone metabolism by Fe3O4@ZnO nanocomposites. DETAILED DESCRIPTION

[0037] The technical solution of the present invention is further elaborated in detail below in conjunction with specific embodiments. The parts of the present invention that are not described and disclosed in detail in the following embodiments should be understood as the prior art known or should be known to those skilled in the art.

[0038] The present invention discloses a magnetic nano antibacterial composite and a preparation method and application thereof. The magnetic nano antibacterial composite is a Fe3O4@ZnO nano composite. Figure 1 The figure shows the synthesis schematic diagram of Fe3O4@ZnO nanocomposite. The specific preparation method is as follows:

[0039] S1: Dissolve the iron salt and ferrous salt in hydrochloric acid solution under mechanical stirring. 3+ and Fe 2+The molar ratio of the Fe3O4 nanoparticles is ≥ 1.5, the temperature is raised to 55-65°C, an ammonia solution is added, the precipitated particles are separated, the precipitated particles are dispersed in a tetramethylammonium hydroxide (TMAOH) solution with a pH of 9.5-10.5 to obtain spatially stable magnetic nanoparticles, the precipitated particles are separated again and washed to obtain pure Fe3O4 nanoparticles;

[0040] Among them, the iron salt is one or more of FeCl3, FeCl3·6H2O, Fe2(SO4)3 and Fe2(NO3)3; the ferrous salt is one or more of FeSO4, FeSO4·7H2O, FeCl2 and FeNO3.

[0041] S2: Disperse Fe3O4 nanoparticles in diethylene glycol (English abbreviation: DEG), add diethylene glycol solution of zinc acetate, stir evenly and transfer into a closed reactor, heat to 160-220°C and keep warm for 1.5-2.5h. The reactor after closed heating is a high-pressure environment. The mixture completes the polymerization reaction in this closed and high-pressure environment, and then the suspension after the polymerization reaction is centrifuged at a speed of 7000-10000rpm for 10-18min, washed and magnetically separated to obtain the precipitated particles, so as to obtain the magnetic nano antibacterial complex.

[0042] Example 1

[0043] S1: 12.15 g FeCl3·6H2O (45 mmol) and 8.35 g FeSO4·7H2O (30 mmol, molar ratio Fe 3+ / Fe 2+ ≥1.5) was placed in a 250 mL round-bottom flask and dissolved in 100 mL 0.01 M HCl solution under mechanical stirring; the temperature was then raised to 60°C, and 30 mL 28% ammonia solution was added to the mixture to form a black suspension; finally, TMAOH solution (10% wt) was added to a pH of 10 to obtain magnetic nanoparticles, and the precipitated particles were separated and washed to obtain pure Fe3O4 nanoparticles.

[0044] S2: 50 mg of the Fe3O4 nanoparticles synthesized in step S1 were dispersed in 10 mL of DEG, and added to 100 mL of a 90 mM zinc acetate DEG solution; the mixture was fully mixed by mechanical stirring and placed in a closed reactor, the reactor was placed in an oven, and heated to 180°C for 2 hours. The reactor after the closed heating was a high-pressure environment, and the mixture completed the polymerization reaction in this closed and high-pressure environment; the suspension after the polymerization reaction was then centrifuged at 7500 rpm for 15 min; it was washed four times with ethanol and the precipitated particles were magnetically separated to obtain a Fe3O4@ZnO nanocomposite.

[0045] Example 2

[0046] S1: 12.15 g FeCl3·6H2O (45 mmol) and 8.35 g FeSO4·7H2O (30 mmol, molar ratio FeFe 3+ / Fe 2+ ≥1.5) was placed in a 250 mL round-bottom flask and dissolved in 100 mL 0.01 M HCl solution under mechanical stirring; the temperature was then raised to 55°C, and 30 mL of 28% by weight ammonia solution was added to the mixture to form a black suspension; finally, TMAOH solution (10% wt) was added to a pH of 10.5 to obtain magnetic nanoparticles, and the precipitated particles were separated and washed to obtain pure Fe3O4 nanoparticles.

[0047] S2: 50 mg of the Fe3O4 nanoparticles synthesized in step S1 were dispersed in 10 mL of DEG, and added to 100 mL of a 90 mM zinc acetate DEG solution; the mixture was fully mixed by mechanical stirring, and then placed in a closed reactor, which was placed in an oven and heated to 200°C for 1.5 hours. The reactor after the closed heating was a high-pressure environment, and the mixture completed the polymerization reaction under this high-temperature and high-pressure environment; the suspension after the polymerization reaction was then centrifuged at 10,000 rpm for 10 min; it was washed four times with ethanol and the precipitated particles were magnetically separated to obtain a Fe3O4@ZnO nanocomposite.

[0048] Comparative Example 1

[0049] Preparation of Fe3O4 nanoparticles

[0050] 12.15 g FeCl3·6H2O (45 mmol) and 8.35 g FeSO4·7H2O (30 mmol, molar ratio Fe(III) / Fe(II)≥1.5) were placed in a 250 mL round-bottom flask and dissolved in 100 mL 0.01 M HCl solution under mechanical stirring; the temperature was then raised to 60°C, and 30 mL 28% ammonia solution was added to the mixture to form a black suspension; finally, TMAOH solution (10% wt) was added to a pH of 10 to obtain magnetic nanoparticles, the precipitated particles were separated and washed to obtain pure Fe3O4 nanoparticles.

[0051] Comparative Example 2

[0052] Preparation of ZnO nanoparticles

[0053] After thoroughly mixing 100 mL of a DEG solution containing 90 mM zinc acetate by mechanical stirring, it was placed in a sealed reaction kettle. The reaction kettle was then placed in an oven and heated to 180 °C with the lid closed. After maintaining the temperature for 2 hours, precipitate particles formed in the solution. The mixture was centrifuged at 7500 rpm for 15 minutes; the precipitate particles were washed four times with ethanol and separated, thus obtaining ZnO nanoparticles.

[0054] Next, the properties of the products prepared in the examples and comparative examples were verified as follows:

[0055] <Characterization of Fe3O4@ZnO Nanocomposites>

[0056] The Fe3O4@ZnO nanocomposites prepared in Example 1 presented a microsphere structure with a particle size of about 38 ± 2 nm. It was preliminarily judged that ZnO was successfully attached to the surface of Fe3O4 nanoparticles. In addition, EDS analysis further confirmed that the Fe3O4@ZnO nanocomposites only contained Fe, O, and Zn elements. At the same time, significant characteristic diffraction peaks appeared in the X-ray diffraction pattern and Fourier transform infrared spectrum, both proving that small-sized zinc oxide nanoparticles were successfully attached to the magnetic core of magnetite ( Figure 2 ).

[0057] <Determination of Antibacterial Properties>

[0058] I. Method for Determining Antibacterial Properties

[0059] Antibacterial experiments were carried out on Enterococcus and Pantoea, the dominant bacteria in corn, and Penicillium and Aspergillus niger, the dominant fungi in corn, which were preserved in the laboratory, using the plate counting method and the inhibition zone method with Fe3O4@ZnO nanocomposites, Fe3O4 nanoparticles, and ZnO nanoparticles. The minimum inhibitory concentrations of Fe3O4@ZnO nanocomposites, Fe3O4 nanoparticles, and ZnO nanoparticles against the dominant bacteria and fungi in corn were determined. Taking the Fe3O4@ZnO nanocomposites as an example, the specific experimental method is as follows:

[0060] 1). Determination of antibacterial properties against bacteria by the plate counting method

[0061] The Fe3O4@ZnO nanocomposites were mixed with hot LB agar medium at concentrations of 0, 250, 500, 750, and 1000 μg / mL respectively, and poured into plates for standby. 100 μL of the bacterial suspension was evenly spread on the LB agar plates mixed with the Fe3O4@ZnO nanocomposites, and three parallel experiments were repeated to ensure the accuracy of the experiment. Finally, the coated plates were placed in an incubator and cultured at 37 °C for 1 day.

[0062] 2). Determination of antifungal properties against molds by the inhibition zone method

[0063] The Fe3O4@ZnO nanocomposite was mixed evenly with hot potato dextrose agar (PDA) at concentrations of 0, 2, 4, and 8 mg / mL, and poured into a plate for later use. In the center of the PDA medium containing different concentrations of Fe3O4@ZnO nanocomposite, a fresh mold spore suspension was inoculated. Three parallel tests were repeated for each concentration gradient to ensure the accuracy of the experiment, and sterile water was set as a control group. After the inoculation was completed, the PDA culture dish was placed in a constant temperature environment of 28°C and cultured for 3 days.

[0064] 3) Determination of minimum inhibitory concentration (MIC)

[0065] First, Pantoea and Enterococcus cultured to a specific growth stage (OD 600 of 0.65 and 0.73, respectively) were inoculated into fresh culture medium at a ratio of 2% (v / v). Subsequently, 100 μL of bacterial suspension was added to each 96-well plate. Next, the Fe3O4@ZnO nanocomposite was mixed evenly with LB culture medium at concentrations of 100, 200, 300, 400, 500, 600, 700, 800, 900 and 1000 μg / ml, and irradiated with ultraviolet light for 30 minutes on a clean bench. Subsequently, 100 μL of each concentration of Fe3O4@ZnO nanocomposite suspension was added to the wells containing the bacterial suspension. At the same time, a sterile culture medium without Fe3O4@ZnO nanocomposite was set as a control group. The experiment was repeated three times in parallel to ensure the accuracy of the results. Finally, the 96-well plate was placed in a constant temperature incubator and cultured at 37°C for 12 hours, and then the OD 595 The absorbance value at wavelength.

[0066] To determine the minimum inhibitory concentration (MIC) of mold, the Fe3O4@ZnO nanocomposite was mixed evenly with PDB culture medium at concentrations of 100, 200, 300, 400 and 500 μg / ml, and sterilized by ultraviolet light for 30 minutes on a clean bench. A fresh mold spore suspension was added to a sterile 96-well plate at 100 μL per well. Subsequently, 100 μL of each concentration of Fe3O4@ZnO nanocomposite suspension was taken and dropped into the wells containing the bacterial suspension. In order to ensure the accuracy of the experiment, a culture medium without Fe3O4@ZnO nanocomposite was set as a control group. Three parallel experiments were repeated to ensure the accuracy of the results. Subsequently, the 96-well plate was placed in a constant temperature incubator and cultured at 28°C for 36 hours. Finally, the OD value of each well was measured. 595 The absorbance value at .

[0067] The antibacterial experiments of Fe3O4 nanoparticles and ZnO nanoparticles are generally the same as the antibacterial experimental steps of the above-mentioned Fe3O4@ZnO nanocomposite.

[0068] 2. Results of the determination of antibacterial properties

[0069] Fe3O4@ZnO nanocomposites have strong inhibitory effects on the dominant bacteria Enterococcus and Pantoea and the dominant fungi Penicillium and Aspergillus niger in corn. As the concentration of Fe3O4@ZnO nanocomposites increases, the number of Enterococcus and Pantoea colonies in the culture dish also decreases ( Figure 3 ). When the concentration of Fe3O4@ZnO was 0.25mg / mL, the colony count of Pantoea was less than that of Enterococcus; when the concentration of Fe3O4@ZnO was 0.5mg / mL, Pantoea had almost no growth and the total number of Enterococci was significantly reduced. The results showed that with the increase of Fe3O4@ZnO concentration, the nanocomposite had a significant inhibitory effect on the growth and reproduction of Pantoea, while the inhibitory effect on Enterococcus was relatively weakened. Fe3O4@ZnO nanocomposite had a certain degree of inhibitory effect on the hyphae growth of Penicillium and Aspergillus niger, and the inhibitory effects were different. This is because the different characteristics of the two fungi lead to different antifungal effects ( Figure 4 ). As the concentration of Fe3O4@ZnO nanocomposites increased, the inhibitory effects on both fungi also increased.

[0070] Among them, the minimum inhibitory concentrations of Enterococcus and Pantoea were 0.7 mg / mL and 1.0 mg / mL, respectively. Figure 5 ); the minimum inhibitory concentrations of Penicillium and Aspergillus niger were 400 μg / mL and 500 μg / mL, respectively ( Figure 6 ). With the increase of the concentration of Fe3O4@ZnO nanocomposite, the growth and reproduction of Enterococcus and Pantoea showed a downward trend, and the growth and reproduction of Penicillium and Aspergillus niger also showed a downward trend, indicating that Fe3O4@ZnO nanocomposite has a good inhibitory effect on the dominant microorganisms in corn.

[0071] The MIC of the Fe3O4 nanoparticles prepared in Comparative Example 1 against Aspergillus niger was 2000 μg / mL, and the MIC of the ZnO nanoparticles prepared in Comparative Example 2 against Aspergillus niger was 700 μg / mL. It can be understood that the MIC of the uniformly mixed Fe3O4 + ZnO was 1350 μg / mL. However, the minimum inhibitory concentration (MIC) of the Fe3O4@ZnO nanocomposite prepared in Example 1 of the present invention against Aspergillus niger was 500 μg / mL, which was not only less than the MIC of the uniformly mixed Fe3O4 + ZnO, but also less than the MIC of the ZnO nanoparticles with higher antibacterial properties against Aspergillus niger, indicating that there was a certain synergistic effect in the combination of Fe3O4 nanoparticles and ZnO nanoparticles when inhibiting Aspergillus niger. This was mainly due to the Fe3O4@ZnO nanocomposite prepared based on the magnetic core of Fe3O4, which made the local concentration of ZnO nanoparticles higher. Coupled with the reduction in particle size during the preparation of ZnO nanoparticles, the efficiency of releasing ROS increased, the local concentration increased, and the antibacterial Zn 2+ The release efficiency was improved, further enhancing its antibacterial properties.

[0072] <Inhibition of Fe3O4@ZnO Nanocomposite on the Growth of Microorganisms during Maize Storage>

[0073] The prepared Fe3O4@ZnO nanocomposite was added to maize. Under the conditions of a temperature of 30 °C and a relative humidity of 80%, after 42 days of simulated storage, the total number of bacterial colonies on the surface of the control group (without addition) maize increased significantly with the extension of storage time (P < 0.01), and the total number of bacterial colonies increased to 1.2×10 4 CFU / mL at the end of the simulated storage, while the total number of bacterial colonies on the surface of the treatment group (added with Fe3O4@ZnO nanocomposite) maize was significantly inhibited ( Figure 7 ). Fungi, especially molds, have a greater impact on the storage quality of maize. During the 42-day simulated storage process, the total number of fungal colonies on the surface of the experimental group maize remained at a relatively low level, while the total number of fungal colonies in the corresponding control group increased significantly ( Figure 8 ). The research data showed that the constructed Fe3O4@ZnO nanocomposite could not only inhibit the growth and reproduction of bacteria during maize storage, but also effectively inhibit the growth and reproduction of fungi.

[0074] <Inhibition of Fe3O4@ZnO Nanocomposite on the Content of Mycotoxins during Maize Storage>

[0075] The prepared Fe3O4@ZnO nanocomposite was added to corn. After 42 days of simulated storage at a temperature of 30°C and a relative humidity of 80%, the mold on the surface of corn in the control group grew rapidly and metabolized to produce a large amount of mycotoxins, causing the contents of aflatoxin B1 (AFT B1), vomitoxin (DON), and zearalenone (ZEN) to reach the highest levels of 7.8 mg / kg, 3.1 mg / kg, and 3.1 mg / kg, respectively. Fig. 9 , Fig.10 , Fig.11 ). The Fe3O4@ZnO nanocomposite was added to the experimental group. While inhibiting the growth and reproduction of mold, it significantly reduced the content of mycotoxins, avoided the stimulation of mycotoxins metabolism by the stress effect, and kept the mycotoxins content at a low concentration. The Fe3O4@ZnO nanocomposite has an inhibitory effect on the metabolism of toxins by toxin-producing fungi during corn storage. It is achieved not only by inhibiting the growth and reproduction of toxin-producing fungi during storage, but also by interfering with the process of mycotoxins produced by toxin-producing fungi, affecting the activity of related enzymes and the expression of toxin-producing genes, thereby inhibiting the metabolic toxin production process of toxin-producing fungi. Regardless of the inhibition principle, the results show that the addition of Fe3O4@ZnO nanocomposite can effectively inhibit the growth of microorganisms and mycotoxins metabolism during corn storage, ensuring the safety and stability of corn storage.

[0076] When the magnetic nano antibacterial composite prepared by the present invention is applied to corn storage, the magnetic nano antibacterial composite suspension is evenly sprayed on the surface of the corn, or the magnetic nano antibacterial composite powder is evenly mixed in the corn pile, and the anti-mildew and antibacterial effects are played through the contact effect. When the storage is completed and the recovery is carried out, since the Fe3O4@ZnO nanocomposite material is magnetic, these antibacterial agents can be separated from the corn by an external magnet or a magnetic recovery device, so as to achieve collection and reuse. This method not only improves the economy of the use of antibacterial materials, but also reduces the cost of antibacterial, and is more in line with the requirements of sustainable development while maintaining efficiency. For the agricultural product storage industry, the present invention provides an anti-mildew and antibacterial solution that is both environmentally friendly and economical.

[0077] The above description of the disclosed embodiments enables one skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to one skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.

Claims

1. A method for preparing a magnetic nano antibacterial composite, characterized in that: The following steps are involved: S1: dissolving iron salt and ferrous salt in hydrochloric acid solution, heating, adding ammonia solution dropwise, separating the generated precipitated particles, dispersing the precipitated particles in tetramethylammonium hydroxide solution, separating the precipitated particles again and washing them to obtain Fe3O4 nanoparticles; S2: Disperse Fe3O4 nanoparticles in diethylene glycol, add diethylene glycol solution of zinc acetate, stir evenly, heat to 160-220°C in a sealed container and keep warm for 1.5-2.5 hours, wash, and magnetically separate the precipitated particles to obtain the magnetic nano antibacterial complex.

2. The method for preparing a magnetic nano antibacterial complex according to claim 1, characterized in that: The iron salt in step S1 is one or more of FeCl3, FeCl3·6H2O, Fe2(SO4)3 and Fe2(NO3)3; the ferrous salt is one or more of FeSO4, FeSO4·7H2O, FeCl2 and FeNO3; the added Fe 3+ and Fe 2+ The molar ratio is ≥1.

5.

3. The method for preparing a magnetic nano antibacterial complex according to claim 1, characterized in that: In step S1, after the iron salt and the ferrous salt are dissolved in the hydrochloric acid solution, the temperature is raised to 55-65° C., and then the ammonia solution is added.

4. The method for preparing a magnetic nano antibacterial complex according to claim 1, characterized in that: In step S1, the pH of the tetramethylammonium hydroxide solution is 9.5-10.

5.

5. The method for preparing a magnetic nano antibacterial complex according to claim 1, characterized in that: In step S2, the mixture is sealed and heated to 180-200°C and kept warm for 1.5-2h.

6. The method for preparing a magnetic nano antibacterial complex according to claim 1, characterized in that: In step S2, after heat preservation, centrifugation is performed to obtain a precipitate, which is then washed. The rotation speed of the centrifugation is 7000-10000 rpm, and the centrifugation time is 10-18 min.

7. A magnetic nano antibacterial composite, characterized in that: The magnetic nano antibacterial composite is prepared by the preparation method described in any one of claims 1 to 6.

8. Use of the magnetic nano antibacterial complex as claimed in claim 7 as a bacterial or fungal antibacterial agent.

9. An application of the magnetic nano antibacterial composite as claimed in claim 7 in corn storage, characterized in that: The magnetic nano antibacterial complex is sprayed or stirred and dispersed on the surface of corn kernels.

10. An application of the magnetic nano antibacterial composite as claimed in claim 9 in corn storage, characterized in that: The magnetic attraction, movement and adsorption recovery of the nano antibacterial complex are achieved by placing magnets at fixed points.

Citation Information

Patent Citations

  • Adsorbent based on ferroferric oxide and nano zinc oxide and preparation method for adsorbent

    CN104815610A

  • Fe3O4 / ZnO nanocomposite and synthetic method thereof

    CN109225236A